1998
DOI: 10.2527/1998.76102619x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forage vs grain feeding on carcass characteristics, fatty acid composition, and beef quality in Limousin-cross steers when time on feed is controlled.

Abstract: Limousin-cross steers ( n = 135; 258 ± 26 kg) were used to compare forage vs grain feeding on carcass composition and palatability attributes of beef when time on feed was controlled. Diets included a 95% alfalfa silage ration (AS) or a 68% highmoisture corn, 25% alfalfa silage ration (HMC). These were incorporated into six treatments to allow comparisons of end points based on similar days on feed or backfat finish. Dietary treatments included 1 ) HMC ( 4 mm), or cattle allowed ad libitum intake of HMC until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
104
3
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(133 citation statements)
references
References 41 publications
(112 reference statements)
21
104
3
5
Order By: Relevance
“…Indeed, no significant difference in juiciness has been observed between grass-fed and grain-fed young bulls despite differences in carcass fatness and meat tenderness [114]. Similarly, no significant difference has been observed in juiciness of meats of young bulls fed either an alfalfa silage-diet or a concentrate-diet indoors [66]. However, meat from the Longissimus thoracis and Semitendinosus muscles of young bulls fattened with hay is more juicy than meat from muscles of young bulls fed grass silage [61].…”
Section: Juicinessmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, no significant difference in juiciness has been observed between grass-fed and grain-fed young bulls despite differences in carcass fatness and meat tenderness [114]. Similarly, no significant difference has been observed in juiciness of meats of young bulls fed either an alfalfa silage-diet or a concentrate-diet indoors [66]. However, meat from the Longissimus thoracis and Semitendinosus muscles of young bulls fattened with hay is more juicy than meat from muscles of young bulls fed grass silage [61].…”
Section: Juicinessmentioning
confidence: 90%
“…The differences in tenderness can be explained by differences in growth rate, fatness or age. To avoid the last two effects, meat from steers fed the 2 previous types of diets have been compared to animals being slaughtered at various ages and with various fatnesses [66]. The meat tenderness of the two types of animals, after correction by taking into account these 2 factors, were not significantly different.…”
Section: Variations Of Diet Compositionmentioning
confidence: 99%
“…Beef content includes lipids and various biomolecules, such as fatty acids. Fatty acid composition is related to the taste and flavor of beef (Westerling and Hedrick, 1979;Melton et al, 1982;Mandell et al, 1998). Therefore, the quality of fat as measured by fatty acid composition and fat melting point (MP), which has a high correlation with fatty acid composition, is one of the most important factors affecting beef quality.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid composition is influenced by sex (Yoshimura and Namikawa, 1985;Zembayashi et al, 1995), diet (Melton et al, 1982;Mandell et al, 1998) and age (Huerta-Leidenz et al, 1996). Genetic influences, such as breed (Yoshimura and Namikawa, 1985;May et al, 1993) and sire (Xie et al, 1996), have also been reported, including sire-based differentiation in Japanese Black cattle (Oka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Duckett et al 1993;Camfield et al 1997) and finishing regime (e.g. Mandell et al 1998) on fatty acid composition; although these studies have been restricted to animals raised in 1 environment. We are not aware of studies that have examined the effect of changing nutrition levels during the grow-out period (from weaning to finishing).…”
Section: Introductionmentioning
confidence: 99%